Employee Attrition in ITeS Call Centers in Selected Clusters of North India - Kaur, Gagandeep (My University, 2014)
Indian Information Technology-Business Process Management (IT-BPM) sector has been growing at a fast pace. The main functional areas of this sector are customer care, finance and administration, human resources and payment services like employee leasing and content development. But, customer care is the most important functional area. About 70% of Indian BPO industry’s revenue comes from ITeS call-centers, 20% from high-volume, low-value data work and the remaining 10% from highervalue information work (Nayanathara, 2007). India is the only country that offers the depth and breadth of offerings across different segment of this industry – IT Services, BPM, Engineering & R&D, Internet & Mobility and Software Products. IT Services is a USD 50 billion sector, BPM is a USD 20 billion sector, Engineering crossed USD 10 billion and Software products, Internet & Mobility are emerging opportunities (NASSCOM, 2014). The Indian IT-BPM industry exports expected to reach USD 84-87 billion - growth rate of 12-14% where as domestic revenues to grow by 13-15% and reach INR 1180-1200 billion (NASSCOM, 2014). The Indian IT-BPM sector continues to be one of the largest employers in the country directly employing nearly 3 million professionals, adding over 180,000 employees (NASSCOM, 2013). Human capital is the most important driver for the success of any organization. No doubt, available talent pool is the backbone for Indian BPO industry. Due to cheap labor in Asian countries, the United States of America and United Kingdom are outsourcing their non-core/core business activities to Indian firms. Thus, it generates many employment opportunities for people (18-50 years) in India having fluency in English. The management of the ITeS call centers provides many benefits to their employees. Despite many benefits given to the employees of the Indian ITeS call centers, the industry is facing many issues. Nowadays, the most important issue in ITeS call center industry is employee attrition. It has been increasing since the inception of the outsourcing sector in India. Employee attrition can be defined as a reduction in the number of employees through retirement, resignation or death. It may also be understood as separation of an employee by any other means. Although many researchers have tried their level best to find out the reasons and solutions for the same, but no one yet has come up with a proper remedy for this ever increasing problem of employee attrition. The researchers have failed to focus on ‘what actually the employees of ITeS call centers are looking for? The present study analyzes the existing attrition scenario in ITeS call centers. But, the prime concern of this research is to identify the key factors responsible for employee attrition. This has been achieved through a well-structured comprehensive questionnaire to identify the factors responsible for employee attrition. After identification of these key factors, retention strategies are suggested, to tackle the problem of attrition. A five point Likert scale has been employed for identifying the key factors responsible for employee attrition through questionnaire. The data was analyzed using factor analysis, t-test, AHP and step-wise multiple regression analysis. Based on the primary data and secondary data sources, it has been found that the employee attrition rate is highest in case of ITeS call center industry, in comparison to all the other Indian sectors. A total of eleven factors are extracted through factor analysis. These are: manager’s attitude, work culture, customer handling interface, night shift and personal growth opportunities, nature of the job profiles, health hazards and stress problems, performance management systems, training and development techniques, salary structure and monetary incentives, job satisfaction, nepotism and social recognition. Further, step wise regression analysis was conducted to extract important predictors for employee attrition. Employee attrition is the dependent variable and the independent variables of the study are the eleven factors identified through factor analysis. The predictors of the model are: salary structure and monetary benefits, health hazards and stress problems, job satisfaction and nature of the job profiles. These four variables explain 28.1 percent of variation. Based on the factor analysis results, employee retention strategies were classified into i) professional development programs, ii) employee engagement and other HR Initiatives. There was another question for ITeS employees in the questionnaire, i.e., ‘What will make you stay for a longer tenure in their organizations?’ Majority of the respondents supported higher salaries along with timely promotions and fair performance management systems for retention. Further, they preferred good personal growth opportunities along with challenging job profile. A conducive work culture and cooperative bosses were also next in priority. Therefore, the management of the ITeS call centers should emphasis on all the above listed factors so that the employee retention can be improved.
Ph.D, SOM, Thesis
Keywords: ITeS call centers; employee attrition; IT-BPM; HR; Management